The internationalization of venture capital and private equity - Joshua Aizenman; Jake Kendall (University of California, Economics Department, 2008)
This paper investigates the internationalization of venture capital (VC) and private equity (PE) investments. We derive flows between countries of VC and PE investments worldwide, relying on comprehensive firm-level data sources, covering three decades and about 100 countries. A gravity analysis indicates that distance, common language, and colonial ties are significant factors in directing these flows. Additionally, the presence of high-end human capital, a better business environment, high levels of military expenditure, and deeper financial markets are important local factors that attract international venture capital. There is also evidence of path dependency and persistence in VC and PE flows, indicating network effects and fixed costs of entry may be at work. Further analysis suggests the internalization of VC and PE is an ongoing story. Prior to the 1990s, VC was primarily a US-only phenomenon. The globalization of IT activities induced the US venture capital industry to mature, and to start exporting its unique skills as VC managers. The US is now a dominant net exporter of deals, though most crossborder deals are still either to or from the US. China has emerged as the dominant net importer, followed by Sweden, Canada, the UK, India and France. For deals outside the US, cross-border participation has been the norm, while US-located deals have been almost exclusively domestic, involving a higher percent of international participation only after 2001. In the past few years, domestic VC and PE capacity has begun to emerge in many countries where it did not exist previously.
Keywords: F15; F21; 330; venture capital; gravity equation; path dependence; cross border flows; Kapitalmobilität; Globalisierung; Technischer Fortschritt; Direktinvestition; Risikokapital; Private Equity; Welt